Natural convection in an enclosure containing a sinusoidally heated cylindrical source - Roslan, Rozaini (Elsevier, 2013)
The problem of unsteady natural convection induced by a temperature difference between a cold outer square enclosure and a hot inner circular cylinder is studied in this paper. The cylinder temperature is assumed to vary sinusoidally with time about a fixed mean temperature. The coupled momentum and energy equations have been solved ~iumericallyo ver a wide range of values of the amplitude and the frequency of the source temperature signal, as well as the source radius. It 1s found that the heat transfer rate tends to increase by oscillating the source temperature signal. The maximum heat transfer augmentation was obta~nedfo r frequency between 25x and 30n for a high amplitude and a moderate source radius.